Tingkat keparahan penyakit COVID-19 pada penerima vaksin influenza pada pegawai Kejaksaan Tinggi Provinsi Kalimantan Tengah - Salsabilah, Alfisa Fitri; Carmelita, Austin Bertilova; Toemon, Angeline Novia (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Influenza virus is a common respiratory tract infection with mild to severe clinical manifestations. Influenza and COVID-19 produce similar clinical symptoms and affect the same groups, namely age, gender and high-risk groups. Influenza vaccine effectiveness varies by group by about 40-60%. Individuals who get the influenza vaccine receive protection against COVID-19. The method used for sampling in the population is a simple random sampling method. The total number of respondents is 61 employees of the High Court of Central Kalimantan Province in 2020 and 2021 who have met the inclusion and exclusion criteria. The conclusion of this study is that there is a significant relationship between the administration of the influenza vaccine and the severity of the COVID-19 disease.